Efficacy of botulinum toxin A combined with extracorporeal shockwave therapy in post-stroke spasticity: a systematic review - Ya-nan Du; Yang Li; Ting-yu Zhang; Nan Jiang; Ying Wei; Shi-huan Cheng; He Li; Hao-yang Duan (Frontiers in Neurology, 2024)
ObjectivesIn recent years, there has been an increase in the number of randomized clinical trials of BTX-A combined with ESWT for the treatment of post-stroke spasticity. This has made it possible to observe the benefits of combination therapy in clinical practice. Therefore, this paper reviews the effectiveness of BTX-A in combination with ESWT for the treatment of post-stroke spasticity.MethodsBy October 2023, a systematic review was conducted in the databases PubMed, Cochrane, Embase, Medline, Web of Science, China National Knowledge Infrastructure, Wan Fang Database, China Biology Medicine disc and China Science and Technology Journal Database were systematically searched. We included randomized controlled trials that reported outcome metrics such as MAS, FMA, and MBI score. Studies were excluded if MAS was not reported. The quality of the included studies was assessed by the Cochrane Collaboration’s tool for assessing risk of bias, and the AMSTAR quality rating scale was selected for self-assessment.ResultsA total of 70 articles were included in the initial search, and six were ultimately included. The results of the included studies showed that the combination therapy was effective in reducing MAS scores and improving FMA and MBI scores in patients with spasticity compared to the control group. Combination therapy has also been shown to improve joint mobility and reduce pain in spastic limbs.ConclusionCumulative evidence from clinical randomized controlled trial studies suggests that the combination therapy is effective in reducing lower limb spasticity and improving mobility after stroke. However, more clinical trials are still needed to corroborate the evidence regarding the efficacy of BTX-A combined with shockwave therapy.Systematic Review RegistrationThe system review can be searched in the PROSPERO database (CRD42023476654).